TIME AS A COORDINATE VARIABLE - Althubyani, Hassan R.; Nawafleh, Khaled I. (European Scientific Journal, ESJ, 2012)
We have investigated the equations of motion for parametrized invariant Lagrangian systems. We applied the technique of separation of variables and the method of canonical transformations to solve the Hamilton-Jacobi equation. The quantization of parametrized invariant Lagrangian systems is investigated using the WKB approximation.